Investigations on the Anticancer Potential of Benzothiazole-Based Metallacycles - Mokesch, Stephan; Cseh, Klaudia; Geisler, Heiko; Hejl, Michaela; Klose, Matthias H. M.; Roller, Alexander; Meier-Menches, Samuel M.; Jakupec, Michael A.; Kandioller, Wolfgang; Keppler, Bernhard K. (Frontiers in Chemistry, 2020)
A series of 2-phenylbenzothiazole derivatives and their corresponding organometallic ruthenium(II) and osmium(II) complexes were synthesized, designed to exploit both, the attributes of the half-sandwich transition metal scaffold and the bioactivity spectrum of the applied 2-phenylbenzothiazoles. All synthesized compounds were characterized via standard analytical methods. The obtained organometallics showed antiproliferative activity in the low µM range and are thus at least an order of magnitude more potent than the free ligands. ESI-MS measurements showed that the examined compounds were stable in aqueous solution over 48 h. Additionally, their binding preferences to small biomolecules, their cellular accumulation and capacity of apoptosis/necrosis induction were investigated. Based on the fluorescence properties of the selected ligand and the corresponding ruthenium complex, their subcellular distribution was studied by fluorescence microscopy, revealing a high degree of colocalization with acidic organelles of cancer cells.